Desempenho agronômico de cebola em função da adubação fosfatada - Silva, Luiz Ricardo Rebouças da (Universidade Federal Rural do Semi-Árido, 2018)
Onion has great importance in the national scenario because it occupies the third position in quantity produced and income generated among the vegetables. Associated with this, due to absence of an official fertilization recommendation bulletin for State of Rio Grande do Norte, there is a need for studies on the amount of fertilizers that should be applied to main cultivars used in region. Objective of this study was to evaluate the agronomic performance of onion in response to phosphate fertilization.The experiments were installed at the Rafael Fernandes Experimental Farm of the Universidade Federal Rural do Semi-Árido (UFERSA), from July to October 2016 and from June to October 2017. Experimental design was randomized blocks in a 2 x 6 factorial scheme, with four replications. The treatments consisted of the combination of two onion cultivars (IPA11 and Rio das Antas) and six doses of phosphorus (0, 60, 120, 180, 240 and 300 kg ha-1 P2O5). The evaluated characteristics were: Phosphorus content in the diagnostic leaf, dry mass and accumulation of phosphorus in the plant, commercial classification of bulbs, commercial bulb productivity, non-commercial bulb productivity, total bulb productivity, economic phosphorus dose and efficiency indexes nutritional. Data were submitted to analysis of variance and dose effects were evaluated by regression analysis. The increase in phosphorus doses resulted in higher accumulation of phosphorus and dry mass in the plant, with a consequent increase in the total and commercial productivity of bulbs, although the agronomic, physiological, recovery and use efficiency decreased. In general, Rio das Antas hybrid obtained higher productivity when compared to cultivar IPA11, in both cultivation seasons
Keywords: Allium cepa L.; Fósforo; Nutrição mineral de plantas; Eficiência nutricional; Allium cepa L.; Phosphorus;; Mineral nutrition of plants; Nutritional efficiency; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO